Methodology of "artificial control environment" in the process of physical exercise for children with disabilities: theoretical justification and practical application - Serhii Kholodov; Oleh Savlyuk; Anastasiia Hrebenina; Leonid Yarmolinsky; Mykola Kolos (Фізична реабілітація та рекреаційно-оздоровчі технології)
Purpose. The purpose of the study is to systematize and substantiate theoretical knowledge and the results of practical experience in the use of technical means and methodological techniques of the “artificial control environment” in the process of physical exercise for children with disabilities.